Fast preparation of high-performance zero-valent iron biochar materials for the removal of arsenic and antimony pollutants utilizing waste wheat straws - Renxi Fang; Jing Peng; Lanxi Yu; Zepeng Wang; Keliang Pan; Chunjie Yan; Sen Zhou (Carbon Neutrality)
Abstract This study presents an innovative one-step Joule heating pyrolysis strategy for synthesizing zero-valent ferromagnetic biochar composites (BC@20Fe0) through controlled precursor impregnation of wheat straw with FeCl3. The proposed technique overcomes the limitations of conventional tube furnace carbonization by achieving uniform heating with 97.94% reduced energy consumption (35.1 kW·h/kg vs 1706.8 kW·h/kg) and 99.61% shorter processing time (60 s vs 4.3 h). The optimized BC@20Fe0 had adsorption capacities of 100.0 mg/g and 151.5 mg/g for As(V) and Sb(V), respectively, which were about 1.6 and 2.5 times higher than those of the traditional biochar composites. Systematic characterization (XPS, FT-IR, XRD) revealed three synergistic mechanisms: 1) Fe0-mediated redox reactions, 2) surface complexation (Fe–O-As/Sb), and 3) electrostatic-enhanced precipitation. After four regeneration cycles, the material still has a removal rate of over 50% for As and Sb, and can still be magnetically recycled. This breakthrough in energy-efficient synthesis and magnetic separability establishes BC@20Fe0 as a sustainable solution for heavy metal remediation, particularly addressing the critical challenge of simultaneous As-Sb removal in practical wastewater treatment scenarios.